Multi-Fractal Analysis in Problems of the Applied Physics - Chernogor, L. F.; Lazorenko, O. V.; Onishchenko, A. A. (Taras Shevchenko National University of Kyiv, 2023)
According to the non-linear and the system paradigms, many processes generated in open, non-linear, dynamical systems under influence of a powerful source of energy release are appeared to be short-time, ultrawideband, non-linear and fractal. In the paper [1] published one year ago, we have introduced a short review of the existing mono-fractal analysis methods, which can be useful and quitly applicable for solving of the applied physics problems, where there are a lot of such processes and such systems. To investigate their fractal properties more extended, the multi-fractal analysis methods should be applied. Unfortunately, similar the monofractal analysis methods, these methods are often appeared to be quite unknown for the most part of researchers too.